2017
DOI: 10.3389/fpls.2017.01323
|View full text |Cite
|
Sign up to set email alerts
|

In Arabidopsis thaliana Cadmium Impact on the Growth of Primary Root by Altering SCR Expression and Auxin-Cytokinin Cross-Talk

Abstract: Cadmium is one of the most widespread pollutant in both terrestrial and marine environment, and its inhibitory effect on plant growth has been largely demonstrated. However, the molecular mechanisms underlying Cd toxicity in plant and mainly in root, as the first organ sensing soil heavy metals, need to be better investigated. To this aim, in the present work we analyzed the growth and the organization of Arabidopsis thaliana primary root in seedlings exposed to Cd (25 and 50 μM) for 8 days starting from germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 73 publications
4
42
0
Order By: Relevance
“…We found that salt treatment and fip1‐2 mutation affected poly(A) site usage in a significant number of genes associated with the response to cadmium (Table S3a,b). Treating seedlings with Cd, a non‐essential toxic heavy metal, inhibits root growth (Yuan and Huang, ) and affects gene expression (Li et al ., ), probably by affecting SCR expression (Bruno et al ., ) and auxin signaling (Yuan and Huang, ). First, we analyzed whether Cd affects FIP1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…We found that salt treatment and fip1‐2 mutation affected poly(A) site usage in a significant number of genes associated with the response to cadmium (Table S3a,b). Treating seedlings with Cd, a non‐essential toxic heavy metal, inhibits root growth (Yuan and Huang, ) and affects gene expression (Li et al ., ), probably by affecting SCR expression (Bruno et al ., ) and auxin signaling (Yuan and Huang, ). First, we analyzed whether Cd affects FIP1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…IAA8 (INDOLEACETIC ACID-INDUCED PROTEIN8), IAA14, ZmARFs (AUXIN-RESPONSIVE FACTORS), SCR (SCARECROW), and LRP1 (LATERAL ROOT PRIMORDIUM PROTEIN1) were reported to be involved in root development, especially lateral root formation (Smith and Fedoroff, 1995;Lim et al, 2005;Krichevsky et al, 2009;Arase et al, 2012;Bruno et al, 2017). The ZmbZIP4 overexpression lines had longer primary roots and seminal roots as well as more lateral roots and LRP than the wild type, while the mutants showed opposite changes (Fig.…”
Section: Multiple Root Development-related Genes Are Targeted By Zmbzip4mentioning
confidence: 99%
“…Cd in soil is easily taken up by plant roots and causes severe phytotoxicity to plants ( Zare et al., 2018 ). Excessive Cd restricts nutrient uptake ( Yamaguchi et al., 2016 ; Wang et al., 2017 ; Cengiz et al., 2019 ; Wu et al., 2019 ), decreases photosynthetic efficiency ( Pereira de Araújo et al., 2017 ), delays seed germination ( Zhang et al., 2014 ), and impairs plant growth and development ( Bruno et al., 2017 ; Sofo et al., 2017 ), resulting in serious production reductions ( Abbas et al., 2018 ; Guo et al., 2018 ; Chen et al., 2019 ). The current study shows that some orchard soils and even fruits have been contaminated by Cd, which threatens the growth of fruit trees and the edible safety of fruits ( Cheng et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%